2011
DOI: 10.1007/s12149-011-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in differentiated thyroid cancer patients with elevated thyroglobulin and negative 131I whole body scan: evaluation by thyroglobulin level

Abstract: Diagnostic accuracy of FDG PET in radioiodine negative thyroid cancer may vary depending on serum Tg levels at imaging. (18)F-FDG PET/CT is useful in detection and localization of recurrent thyroid cancer in patients with negative diagnostic radioiodine scan despite elevated Tg greater than 20 ng/ml or high anti-Tg Ab titers. In contrast, PET/CT provides little additional information when the Tg is less than 5 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
2
23
0
3
Order By: Relevance
“…Moreover, Tg autoantibodies, which could interfere with Tg measurements, were not available for all patients. Na et al (79) reported positive FDG-PET/CT scans in ten of 26 patients (38%) with stimulated Tg levels between 5 and 10 ng/ml, which suggests that FDG-PET/CT might also be useful in patients that have a relatively low stimulated Tg.…”
Section: Controversies and Areas Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Tg autoantibodies, which could interfere with Tg measurements, were not available for all patients. Na et al (79) reported positive FDG-PET/CT scans in ten of 26 patients (38%) with stimulated Tg levels between 5 and 10 ng/ml, which suggests that FDG-PET/CT might also be useful in patients that have a relatively low stimulated Tg.…”
Section: Controversies and Areas Of Uncertaintymentioning
confidence: 99%
“…The specificity of PET alone was found to be 50% vs 89% for PET/CT (76). Although serum Tg levels correlate with tumor load and true-positive FDG-PET/CT scans increase as Tg levels increase, several authors have suggested that a cutoff value of 10 ng/ml for unstimulated Tg is at best a suboptimal criteria for the selection of patients for FDG-PET/CT (77,78,79). Giovanella et al (77) reported true-positive FDG-PET/CT examinations in 14 of 30 patients (46%) with Tg levels of !10 ng/ml, and Vera et al (78) reported FDG-PET/CT positive findings in 20 of 44 DTC patients (45%) with Tg levels of !10 ng/ml during LT4 therapy and with negative DxWBS.…”
Section: Controversies and Areas Of Uncertaintymentioning
confidence: 99%
“…Suspicious recurrent lymph node metastases were detected on the neck, which may suggest that negative 18 F-FDG PET/CT finding may represent a small or well-differentiated metastatic lesions 26 . Subsequently, these patients underwent empirical 131 I therapy using 150 mCi.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our PPV, NPV, and accuracy were 87.04%, 96.00%, and 91.35%, respectively. In a study by Na et al, performed on patients diagnosed with DTC with elevated serum Tg levels despite negative 131 I WBS, the overall sensitivity, specificity, accuracy, PPV, and NPV of 18 FDG PET/CT were 69.4%, 66.7%, 69.1%, 95.6%, and 17.4%, respectively [15]. The sensitivity of 18 FDG PET/CT was 68.4% in another study performed on 61 patients with suspected recurrence [16].…”
Section: Discussionmentioning
confidence: 97%
“…Na et al, examined 18 FDG PET/CT images of 60 DTC patients with elevated serum Tg levels as well as negative radioiodine WBS in 2010. They divided the patients into 4 sub-groups (2 ng/ml ≤ stimulated Tg [sTg] < 5 ng/ml; 5 ng/ml ≤ sTg < 10 ng/ml; 10 ng/ml ≤ sTg < 20 ng/ml; and ≥ 20 ng/ ml)] and found that the sensitivity of PET/CT according to Tg levels was 28.6% when Tg was between 2 and 5, 57.1% between 5 and 10, 60.0% between 10 and 20, and 85.7% when Tg was ≥ 20 ng/ml [15]. In a study by Shammas et al, comprising of 61 DTC patients, the overall sensitivity, specificity, and accuracy of 18 FDG PET/CT were 68.4%, 82.4%, and 73.8%, respectively.…”
mentioning
confidence: 99%